Estimation of the shelf life of red chili sauce with the addition of Onggok cassava flour using the Extended Storage Studies method: [Pendugaan umur simpan saus cabai merah dengan penambahan tepung onggok menggunakan metode Extended Storage Studies] - Renate, Dharia; Lavlinesia, Lavlinesia; Surhaini, Surhaini (Jurnal Teknologi & Industri Hasil Pertanian, 2025)
Chili sauce is a semi-solid product made from high-quality, fresh chili peppers (with a moisture content of 90%) as the main ingredient. The raw material for chili sauce has a high moisture content, is thin, and easily spoils, so a thickening agent is needed to stabilize the sauce, prevent separation between the liquid and solid components, and achieve the desired viscosity. The use of cassava flour in chili sauce formulation can enhance resistance to storage processes, making it more stable during storage. The objective of this study was to determine the shelf life of red chili sauce with onggok cassava flour as a filler using the Extended Storage Studies (ESS) method. The parameters tested to estimate the shelf life of the sauce were moisture content, pH, viscosity, and color, stored for 20 days, with testing conducted every 4 days. The results of the study indicate that using the Extended Storage Studies method, chili sauce with the addition of 2.25% cassava flour has a shelf life of up to 44 days under specific storage conditions with quality criteria of moisture content 83%, pH 3.5, viscosity 1,200-2,400 cP, and color 34.9 °Hue. The results of the study indicate that onggok cassava flour has potential as an effective natural thickening agent to improve the quality and stability of red chili sauce products over a specific storage period.